Efecto del Programa Nutrición de Alto Rendimiento (NAR), complementario a la fertilización química en el cultivo de arroz (Oryza sativa L.), en la zona de Babahoyo - Medina Vargas, Miguel Ángel (2017)
VIII. SUMMARY The present investigation was developed in the lands of the Experimental Farm "San Pablo" of the College of Agricultural Sciences of the Technical University of Babahoyo. The floor is of plane topography, franc-loamy texture and regular drainage. The outlined objectives were: to evaluate the Nutritional program of High Yield (NAR) complementary to a fertilization program, to determine the effect of the NAR in the production of qq/ha of rice and to analyze the grain yield economically for effect of the NAR. In the investigation certified seed of the variety of rice INIAP was used 14, the treatments were evaluated with a program of Nutrition of High Yield, complementary to the chemical fertilization, such as Without NAR; With NAR; NAR-10% of chemical fertilization; NAR-15% of chemical fertilization and NAR-20% of chemical fertilization. The experimental design of Complete Blocks was used at random with five treatments and four repetitions. The comparisons of the stockings were made under the test from Tukey to 95% of probability. To estimate in correct form the effects of the treatments they took the data of plant height to the crop, days to flowering, days to maturation, sprout number for square meter, panicles number for square meter, panicles longitude, grains for panicle, relationship grain/ straw, weight of 1000 grains, yield of the cultivation and economic analysis. For the obtained results it was determined that the Program Nutrition of High Yield (NAR), he/she obtained effects on the production of the cultivation of rice. The treatment where alone NAR was applied it reached bigger averages in the variable plant height, I number of sprout and panicles/m2, panicle longitude and the treatment that flourished was and it matured in smaller time; the treatment that NAR was not applied registered smaller grains/panicle number and relationship grain-straw; the biggest weight of 1000 grains and yield presented it the use of alone NAR and in the economic analysis the application of alone NAR stood out with a gain of $ 763,94.